2022
DOI: 10.3390/ijms23063029
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Percentage of CD14dimCD16+SLAN+ Monocytes Producing TNF and IL-12 as an Immunological Sign of CLL Progression

Abstract: Monocytes are one of the least studied immune cells with a potentially important role in the pathogenesis of chronic lymphocytic leukemia (CLL). Nevertheless, data regarding the role of subpopulations of monocytes in the CLL microenvironment are still limited. For the very first time, this study presents an assessment of monocyte subsets divided according to SLAN and CD16 expression in CLL patients. The study involved 70 freshly diagnosed CLL patients and 35 healthy donors. Using flow cytometry, monocyte subpo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…In humans, non-classical monocytes expressing CD16 are, together with NK cells, essential for ADCC and can kill primary leukemic cells, and CD16 + monocytes from leukemia patients can perform potent ADCC [22]. A recent study of 70 CLL patients indicated that percentages of non-classical CD16 + monocytes decrease with the stage of CLL and are increased in patients bearing good prognostic markers, whereas those patients with reduced percentages are more likely to require treatment, indicating beneficial effects of CD16 + non-classical monocytes on antitumor responses [23].…”
Section: Discussionmentioning
confidence: 99%
“…In humans, non-classical monocytes expressing CD16 are, together with NK cells, essential for ADCC and can kill primary leukemic cells, and CD16 + monocytes from leukemia patients can perform potent ADCC [22]. A recent study of 70 CLL patients indicated that percentages of non-classical CD16 + monocytes decrease with the stage of CLL and are increased in patients bearing good prognostic markers, whereas those patients with reduced percentages are more likely to require treatment, indicating beneficial effects of CD16 + non-classical monocytes on antitumor responses [23].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, VCAN can inhibit the recruitment of monocytes and neutrophils to tumor tissues, thereby reducing the anti-tumor inflammatory response ( Kellar et al, 2021 ). The proteins encoded by CD14, IL1B, and SERPINB1 participate in the innate immune and inflammatory responses, indicating that this monocyte cluster have potential antitumor effects ( Gong et al, 2011 ; Burgener et al, 2019 ; Kim et al, 2022 ; Kowalska et al, 2022 ). On the whole, monocytes exhibit a prevailing immunosuppressive phenotype, aligning with previous investigations.…”
Section: Discussionmentioning
confidence: 99%
“…These authors highlighted the critical role played by IRF5 in osteoclast differentiation: IRF5 overexpression in M2 monocytes indeed decreased their osteoclastogenic potential, whereas their down-regulation by IRF5 silencing enhanced the osteoclastogenic potential of M1 cells [ 42 ]. Interestingly, Kowalska et al recently showed that the “intermediate” monocytes (CD14++CD16+) are the main producer of IL-10 [ 43 ]. This finding may appear in line with our in vivo and in vitro data and may support the hypothesis of a potential relationship among a higher number of “intermediate monocytes”, higher levels of bone erosion found in these patients and the detection of enhanced osteo-clastogenesis by IL-10-driven monocytes.…”
Section: Discussionmentioning
confidence: 99%